Movements of Balance Sheet Items and Liquidity Nexus: Evidence from Serbian Banking Sector - Vesic, Tamara Slavisa; Barjaktarovic, Lidija (Industrija, 2020)
The subject of the research is to determine the liquidity quality of the Serbian banking sector. The aim is to find out what the effect of fluctuation in balance sheet items on the most common liquidity indicators is. The research was carried out on the sample of 10 leading Serbian banks in terms of assets (Intesa, Komercijalna, UniCredit, Societe Generale, Raiffeisen, AIK, Euro Bank Belgrade, Erste, Postanska stedionica and Vojvodjanska), by applying the Pearson’s correlation coefficient. The four most commonly used liquidity ratios were used as dependent variables, while individual balance sheet items (part of the liquidity formula) were used as independent variables. According to the conducted research, Serbian banking sector recorded positive performance, i.e. was sufficiently liquid, from 2001 to 2017. Furthermore, very strong correlation was observed between an increase in cash and an increase in bank liquidity, while there was a moderate correlation between an increase in cash and average total liabilities. Moreover, the increase in loans and receivables from banks and other financial institutions had a significant impact on the increase of liquidity, as well as on the increase in provisions and equity. Finally, the increase in the value of owned property and deposits had a negative impact on liquidity ratios.